Implementation of Da'wah Management Principles in the Development of the Taklim Council of 'Aisyiyah Branch, Andam Dewi District - Fatimah, Aviatri; Soiman, Soiman (Jurnal Dakwah dan Komunikasi, 2024)
The lack of trained and qualified preachers or preachers is often an obstacle to implementing effective da'wah. Apart from that, there is a lack of planning, evaluation and monitoring. This also includes the lack of adaptation of preaching to technology which is still a problem at Masjlis Taklim Aisyiyah Branch. This research aims to find out how the principles of da'wah management are implemented by the 'Aisyiyah branch, what are the inhibiting factors in implementing the principles of da'wah management, and what is the development of the application of da'wah management principles in coaching the taklim assembly in Andam Dewi District. The method used in this research uses a qualitative field research approach, such as interviews, observation and documentation. The results of the research show that the 'Aisyiyah Branch in Andam Dewi District has succeeded in implementing the principles of da'wah management in coaching the taklim assembly. However, there are several challenges that need to be overcome, including a lack of trained and qualified preachers, as well as the need for improvements in planning, evaluation and technology adaptation. This research provides valuable insights for improving the effectiveness of da'wah management in majlis taklim and can be a guide for other da'wah organizations in optimizing their performance.